An Update on Hemocytes in Biomphalaria Snails - Fried, Bernard (Journal of Hematology and Oncology Research, 2016)
The hemocyte is a major immunological cell of molluscs. Much of the immunological phenomena associated with molluscan immunology can be attributed to cellular immunity associated with these cells suspended in the hemolymph. These cells are often referred to as amoebocytes or hemocytes. Such cells are of great importance to immune mechanisms associated withBiomphalaria snails. The Biomphalaria snail is the main vector of the important trematode parasite Schistosoma mansoni. This is a waterborne parasite that affects about 200 million people globally and puts countless other millions at risk of infection. Larval stages of the parasite are released from the snail in tainted waters and the larval cercarial stage actively penetrates the skin of humans and other vertebrates. Larvae migrate via the venous system to vital organs associated with the heaptic portal and mesenteric blood vessels. Larvae develop into sexually mature male and female adult worms that live in major venous blood vessels. The worms mate and produce eggs that lodge in major organs such as the spleen, liver, and intestines. Eggs produce extensive granulomas that cause cirrhosis and other pathological conditions in the affected organs.
Keywords: Biomphalaria; Gastropoda; snails; hemocytes; molluscan blood cells +